The State of Reproductive Medicine in Germany - Diedrich, K.; Strowitzki, T.; Kentenich, H. (Geburtshilfe und Frauenheilkunde, 2012)
In the 1960s and 70s, Germany played a leading role in the field of gynaecological endocrinology, which was reflected by the scientific activity of German universities during this period. More recently, however, a dramatic change occurred, resulting in a decreasing number of publications in this field. This has undoubtedly contributed to the marginal scientific position of Germany in gynaecological endocrinology today. This change is reflected by the decreasing number of university centres carrying out active scientific research in the fields of gynaecological endocrinology, reproductive medicine and andrology. Universities now lack mid- and upper-level faculty staff, as interesting and senior positions in the field of reproductive medicine, andrology and reproductive medicine no longer exist. Moreover, in 1991 the German embryo protection law came into force, which severely curtailed scientific research and blocked scientific efforts in this area. German scientists and, of course, childless couples were cut off from scientific advances, e.g. the possibility of single embryo transfer. Germanyʼs scientific position in the fields of gynaecological endocrinology, reproductive medicine and andrology needs to be strengthened. The creation of appropriate structures in German universities is therefore necessary. These would include important cooperations with private medical practices, which currently account for about 75 % of patient care. The lines of communication between the groups representing reproductive medicine in Germany need to be greatly improved. Moreover, we suggest that an important step would be the development of a general human embryology and fertilisation act which would allow German couples to benefit from the global advances in the field of reproductive technology. Germany must stop its policy of scientific obstruction and permit scientific progress in this field in German universities.
Keywords: gynecological endocrinology and reproductive medicine; research in this area; waiting for a law in reproductive medicine